Efektivitas Psikoedukasi Safe Space Online dalam Menurunkan Skor Perilaku Cyberbullying pada Remaja Generasi Phygital - Shafa Reinina Putri; Maharani Tyas Budi Hapsari (Jurnal Bimbingan dan Konseling Pandohop, 2026)
This study aims to evaluate the effectiveness of the "Safe Space Online: Your Zone, Your Rules" psychoeducation program in enhancing prevention knowledge and reducing cyberbullying behavior among phygital generation adolescents. The research employed a quasi-experimental method with a two-group pretest-posttest design. Participants consisted of 10 junior high school students in Bantul selected through purposive sampling. The instruments utilized were a 45-item Cyberbullying Behavior Scale (α = 0.929) and a module-based knowledge test. Wilcoxon test results for the experimental group indicated a significant increase in knowledge (p = 0.041; mean increased from 83.00 to 92.00) and a significant decrease in cyberbullying behavior (p = 0.043; mean decreased from 111.00 to 86.60). Effect size analysis revealed a value of r = 0.64 for both variables in the experimental group, confirming a large practical impact of the intervention. In contrast, the control group exhibited no significant changes (r = 0.04). This study concludes that structured psychoeducation effectively transforms adolescent digital interactions through deeper internalization of ethics and self-regulation compared to general digital literacy.